A greater focus on metals in biomedicine and neuroscience is needed. Issue 1 (December 2016) - White, Anthony
Abstract Metals have many essential functions in the brain and a large body of evidence supports important roles for altered metal stasis in many brain disorders. However, despite this evidence, acceptance of metals as key mediators of brain dysfunction is largely lacking in mainstream biomedicine. This editorial will outline the possible reasons for this and suggest potential means to improve the acceptance of metals as central players in brain disease.